Design & simulation of passive Si3N4 photonics component – grating couplers - Ahmad Sholehin Juperi (Nanyang Technological University, 2024)
In today’s world, the ever-increasing demand for high-speed data transmission necessitates advancements in data transfer technologies. Photonics offers a promising solution, and silicon photonics on SOI platforms has garnered significant interest within the semiconductor market industry. However, efficient light coupling for these devices remains a challenge due to complex design requirements. Grating couplers, which are passive silicon photonics components, have shown potential solutions for efficient light coupling in silicon photonics.